2012
DOI: 10.1080/0305215x.2012.737782
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective aerodynamic shape optimization of small livestock trailers

Abstract: This article presents a formal optimization study of the design of small livestock trailers, within which the majority of animals are transported to market in the UK. The benefits of employing a headboard fairing to reduce aerodynamic drag without compromising the ventilation of the animals' microclimate are investigated using a multi-stage process involving computational fluid dynamics (CFD), optimal Latin hypercube (OLH) design of experiments (DoE) and moving least squares (MLS) metamodels. Fairings are para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 32 publications
(39 reference statements)
0
26
0
Order By: Relevance
“…A preliminary grid independence study carried out on the baseline trailer ( Figure 6) showed that a hybrid hexahedral-tetrahedral grid consisting of 6.7 million cells led to small discretisation errors (equation 3) of 1.5% and 2.0% for F 1 and F 2 , respectively [10]. As shown in section 2, solutions computed on both hexahedral and polyhedral cell types lead to reduced noise levels compared to tetrahedral cells.…”
Section: Design Of Experiments and Cfd Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…A preliminary grid independence study carried out on the baseline trailer ( Figure 6) showed that a hybrid hexahedral-tetrahedral grid consisting of 6.7 million cells led to small discretisation errors (equation 3) of 1.5% and 2.0% for F 1 and F 2 , respectively [10]. As shown in section 2, solutions computed on both hexahedral and polyhedral cell types lead to reduced noise levels compared to tetrahedral cells.…”
Section: Design Of Experiments and Cfd Methodologymentioning
confidence: 99%
“…The difference with numerical experiments is that the errors (and thus the noise) are repeatable due to their deterministic nature [18]. For optimization studies which require analysis of a wide range of designs (such as those for constructing response surfaces or metamodels) this characteristic can lead to problems in identifying optimum designs [10,13]. These issues have received attention; however, there are no studies dedicated exclusively to numerical noise and the negative impact it can have on CFD optimization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper addresses the aerodynamic drag reduction of vans, which are converted for use as emergency response vehicles (ERVs) to provide patient transport to hospital and within the police service in the UK. There has generally been far less research into aerodynamic improvements for vans [19], however funding constraints arising from the recent financial crisis, coupled with rising fuel prices, have forced public authorities in the UK to address the aerodynamic design of their ERVs. For example, the Yorkshire Ambulance Service Trust (YAST) fleet has 1500 ERVs travelling 40 million miles every year, resulting in the consumption of 4.2 million liters of fuel at a cost of more than £6 million.…”
Section: Introductionmentioning
confidence: 99%
“…A separate numerical study (based on the same geometry considered in this paper) demonstrated the potential of this solution through an aerodynamic shape optimisation study (Gilkeson et al, 2013). The results predicted an appreciable 5.3% reduction in aerodynamic drag, with a minor improvement in the heat stress experienced by sheep on the lower deck.…”
Section: Recommended Design Improvementsmentioning
confidence: 99%